Kakawin Arjuna-wiwaha dan pembangunan di masa kini - Padmapuspita Y. (Yayasan Ilmu Pengetahuan dan Kebudayaan "Panunggalan," Lembaga Javanologi, 1988)
On the relevancy of the teachings of Empu Kanwa's Arjuna wiwaha of the 11th century with today's socioeconomic conditions in Indonesia.